The influence of immediate complete anterior guidance development technique on subjective symptoms in Myofascial pain patients: Verified using digital analysis of occlusion (Tek-scan) for analysing occlusion: A 3 years clinical observation - Prafulla Thumati (Wolters Kluwer Medknow Publications, 2015)
Objectives: The purpose of this study is to evaluate the effect of occlusal equilibration using immediate complete anterior guidance development (ICAGD) technique by Kerstein and Farrell on the subjective symptoms of myofascial pain. This technique is the most advanced verifiable and measurable way of digitally analyzing the occlusion using T-scan technology. The primary objective is to reduce the anterior disclusion time to <0.4 s and the secondary objective is to reduce the signs and symptoms of myofascial pain. Materials and Methods: This study is to assess the reducing effects of subjective symptoms of 100 patients diagnosed as myofascial pain patients treated by ICAGD technique as described by Kerstein and Farrell. The common complaints of the patients were a pain in the masseter and temporal muscles, jaw tiredness in the mornings, night bruxing and difficulty in chewing. In this technique occlusal equilibration involves removal of posterior interferences and establish anterior guidance. The patients were treated over three visits 1-week apart and followed for 3 years with an interval of 3 months for the subsequent visits. A visual analog ordinal scale is used to rate the symptoms. The symptoms reduction occurred for all the patients after the first correction in about 5-10 days. In about a period of 3 years review, no recurrence was seen of the chronic myofascial symptoms. Results: In spite of the chronic nature of the patient's symptoms, symptom reduction occurred in a week's time. This was assessed by the results of the ordinal scale values. This agrees with the studies of Kerstein and Farrell. Conclusion: Equilibration of occlusion using digital analysis by T-scan in which force is quantified against time, should be done to establish free functional movements without any interference; otherwise the disturbances in the excursive movements may lead to muscle dysfunction at later years.